The Case for a Complete Model of Strategic Resource Utility in Sport and Entertainment Management - Theodore M. Hayduk III (Journal of Applied Sports Management, 2017)
A complete model of strategic resource utility can be useful for managers in the sport and entertainment industry. In recent years, this industry has been characterized by rapid evolution, high fragmentation, and ubiquitous digitalization, which all highlight the importance of making rapid and informed strategic decisions. Thus, the complete model will help managers quantify their firm’s resource bundle and use a common language during the strategic decision making process. Two industry-specific examples are given to facilitate interpretation of the complete model. Subscribe to JASM
Keywords: Strategic Management; Resources; Sport; Entertainment